Spiritual Coping Relationship With Stress Level In Patients With Chronic Rental Failure (CRF) In RSU Haji North Sumatra Province Year 2022 - Muslimah Pase (Sean Institute, 2023)
Spiritual coping is a way for individuals to use their beliefs in managing anxiety and problems in life. The purpose of this study was to determine the relationship between spiritual coping and stress levels in patients with chronic kidney failure (CKD) at the Haji Hospital in North Sumatra Province in 2022. This study used a correlation description design, the population of this study was 26 people with a total sample of 26 people using accidental sampling technique. Data were obtained through a spiritual coping and stress questionnaire. The data was processed using the Spearman rho test and presented in the form of a frequency distribution table. Research results obtained influence with a significance value or sig. (2-tailed) of 0.000 <0.05, which means that there is a relationship between spiritual coping and stress levels in patients with chronic kidney failure (CKD) at RSU Haji, North Sumatra Province in 2022. The conclusion of this study is that there is a relationship between spiritual coping and stress levels in patients with chronic kidney failure (CKD) at Haji General Hospital in North Sumatra Province in 2022. It is hoped that families will pay attention to spiritual coping given to patients with chronic kidney failure